0176 Perspectives of the value of interprofessional simulation training by participant background. (2nd November 2015) - Forshaw, Natalie; Lane, Mary; Lofton, Lydia; Burmester, Margarita
Abstract : Background: Interprofessional simulation-based team training has been highlighted as a means to improve team performance, 1 The Simulated interPRofessional Team training programme (SPRinT) has published data on the effectiveness of such programmes. 2 We aimed to explore and understand participant perspectives on the value of the interprofessional aspects of simulation in our established programme. Methodology: Participants attending SPRinT courses completed questionnaires on five common themes related to interprofessional simulation, indicating their level of agreement with statements. Results were analysed according to three general professional groups; nursing staff, medical staff and anaesthetists. Results: Data was collected from 64 staff during 10 consecutive courses (91% response rate). The professional groups comprised 10 anaesthetists, 26 nursing staff and 22 medical staff. Medical and nursing groups indicated most of their previous simulation experience was with participants from mixed professional backgrounds (82% and 85% respectively). Anaesthetists indicated most previous simulation training had been with their own profession only (70%). All groups indicated similar levels of agreement that simulation improved their awareness of other professional's roles (All groups: 100% agreement), helped break down workplace barriers (anaesthetists: 100%, nurses: 94%, medical: 91%) and improved their interprofessional team-working ability (anaesthetists: 100%, nurses: 100%, medical: 96%). Anaesthetists indicated that their specific technical training needs may be better met in solo profession simulation. This trend was not seen in the other groups. There was no distinct agreement amongst any groups as to whether participants felt more comfortable participating in groups of the same or multi-professional backgrounds. Conclusions: Our results show all participants valued the opportunity for interprofessional simulation training, particularly in regards to increasing awareness of team members' roles, breaking down barriers and improving working relationships. Anaesthetists highlighted the on-going need for single profession simulation when focusing on specialty-specific technical skills. Good team functioning has been demonstrated to improve patient outcome in critical incidents. Our results support the role for interprofessional simulation training in improving team cohesiveness. References: A review of simulation-based interprofessional education. Clin Simulat Nurs 2011;7(4):117–126 Stocker M, et al . Impact of an embedded simulation team training programme in a paediatric intensive care unit: a prospective, single centre, longitudinal study. Intensive Care Med 2012;38(1):99–104